Mutations of the RNA-Specific Adenosine Deaminase Gene (DSRAD) Are Involved in Dyschromatosis Symmetrica Hereditaria - Miyamura, Yoshinori (The American Society of Human Genetics, 2003)
Dyschromatosis symmetrica hereditaria (DSH) (also called “reticulate acropigmentation of Dohi”) is a pigmentary genodermatosis of autosomal dominant inheritance characterized by a mixture of hyperpigmented and hypopigmented macules distributed on the dorsal aspects of the hands and feet. To determine the gene responsible for this disease, we performed a genomewide search in three families with DSH and mapped the DSH locus to chromosome 1q21.3. The mutations involved in causing DSH have been identified in the gene that encodes double-stranded RNA-specific adenosine deaminase (DSRAD) as the disease gene.